Pengembangan Media Pop_Up Book Pada Materi Metamorfosis Kelas IV Sekolah Dasar - Rizqi Wulandari; Ratih Asmarani (IJPSE : Indonesian Journal of Primary Science Education, 2023)
The creation of pop-up book media for metamorphosis is one of the techniques by which the classroom learning process can be facilitated. This research on media development is motivated, in part, by the demand for innovative and user-friendly learning tools to enhance the classroom learning process. The goal of the researcher in developing pop-up book media is to: (a) Understand the process of developing pop-up book learning media on metamorphosis material; (b) understand the quality of developing pop-up book learning media on metamorphosis material; and (c) understand the implementation of developing pop-up book learning media on metamorphosis material. Research and Development is the method employed in this study (R&D). The approach employed by the researcher is the 4D (four-D) development model, which includes four steps in the development process: define, design, develop, and disseminate. The research procedure is conducted in accordance with the researcher-modified stages of the 4D development model. 88.98% of instrument, material, and media specialists were consulted during the research process for developing pop-up book medium. As a consequence of the implementation phase, researchers got a mean score of 94.18 percent based on responses from educators and students. In addition, the researcher received a score of 92.82 percent based on the average of the expert validation and implementation stages, indicating that the media he or she created met the extremely valid requirements and deserved to be implemented without modification.